Evaluating Batch Imaging as a Method for Non-Lethal Identification of Freshwater Fishes - Conrad James Pratt; Nicholas E. Mandrak (Fishes)
Freshwater fish community surveys are an important component of aquatic ecosystem management. However, the standard method for taxonomic identification currently used for these surveys, wherein fishes are manually identified in the field by a taxonomic expert, has several shortcomings. These include handling-related fish injury and mortality, the need for a fish-identification expert to be present during field sampling, and additional fish mortality due to physical voucher collection. These shortcomings may be overcome using new methods such as environmental DNA (eDNA) or image analyses. While eDNA can provide fish community data through metabarcoding, it is costly and provides little ecological information. A novel, image-based method for taxonomic identification (“batch-image identification”), which addresses the shortcomings of standard and eDNA methods, was tested in this study. Fishes were captured in the field and photographed in small groups (“batches”) within fish viewers for subsequent identification by taxonomic experts. Comparing taxonomist-based identifications from batch images to specimen-based identification, batch-image identification yielded an overall species-level correct-identification rate (CIR) of 49.7%, and an overall genus-level CIR of 61.2%. CIR increased with taxonomist expertise, reaching 83% when identification was performed by expert taxonomists. Batch-image identification data also produced rarefaction curves and fish-length measurements comparable to those obtained through standard methods. Potential methodological improvements to batch-image identification, including procedural adjustments and alternative identification methods, provide direction for the continued testing and improvement of this method.